Immediate effects of neurodynamic nerve gliding versus static stretching on hamstring neuromechanical properties - Satkunskiene, D.; Khair, R. M.; Muanjai, P.; Mickevicius, M.; Kamandulis, S. (European Journal of Applied Physiology, 2020)
Purpose: We investigated the immediate effects of neurodynamic nerve gliding (ND) on hamstring flexibility, viscoelasticity, and mechanosensitivity, compared with traditional static stretching (ST). Methods: Twenty-two physically active men aged 21.9 ± 1.9 years were divided randomly into two equal intervention groups using ST or ND. An isokinetic dynamometer was used to measure the active knee joint position sense, perform passive knee extension, record the passive extension range of motion (ROM) and the passive-resistive torque of hamstrings. Stiffness was determined from the slope of the passive torque-angle relationship. A stress relaxation test (SRT) was performed to analyze the viscoelastic behavior of the hamstrings. The passive straight leg raise (SLR) test was used to evaluate hamstring flexibility. Results: A significant interaction was observed for ROM and passive ultimate stiffness, reflected by an increase in these indicators after ND but not after SD. SLR increased significantly in both groups. After ST, a significantly faster initial stress relaxation was observed over the first 4 s. than after ND. There was no significant change in the active knee joint position sense. Conclusions: ND provided a slightly greater increase in hamstring extensibility and passive stiffness, possibly by decreasing nerve tension and increasing strain in connective tissues than ST. The ST mostly affected the viscoelastic behavior of the hamstrings, but neither intervention had a significant impact on proprioception.